Tindak Tutur Direktif dalam Siniar “Bapak-Bapak: Tinggal dan Menetap di Bali, Fajar Nugra Belum Move on?” pada Kanal YouTube Has Creative - Apriyanni, Rizky Nur Aulia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research analyzes directive speech acts in the webinar titled “Bapak-Bapak: Tinggal dan Menetap di Bali, Fajar Nugra Belum Move On?” broadcasted through the Has Creative YouTube channel on October 20, 2023. The study focuses on non-numeric or non-numeric data using a qualitative approach, examining conversations between Arief Didu as the host and Fajar Nugra as the guest, specifically concentrating on types of directive speech acts. The data collection method used in this research comprises three phases: preparation, implementation, and report writing. The analysis results reveal six types of directive speech acts: requests, questions, commands, prohibitions, permissions, and advice. Sixteen conversation excerpts were identified as instances of directive speech acts, with question speech acts being the most dominant, occurring six times. This research provides a profound insight into the manifestation of directive speech acts in the webinar, aiming to enhance understanding of communication in this format.